Integration Of Remote Sensing And Geophysical Methods In Identifying Shallow Archaeological Remaining Structures At Sungai Batu, Lembah Bujang, Kedah, Malaysia - Ismail, Nurina Auni (2020)
Bujang Valley which is also known as Kedah Tua is believed to be the earliest entrepot and religious center in the Malaysia. Its role can be proved by the discovery of archaeological evidence such as the discovery site of Hindu-Buddhist temples, broken ceramics and many other artefacts related with the trade. The aim of this study is to identify the buried structure area that has great archaeological potential at Sungai Batu by using remote sensing and geophysical methods at four different areas which are SB2ZZ, SB1, SB2 and SB3. Two main characters that can be observed on the surface are mound area and exposed clay bricks. Remote sensing was applied to the whole study area by using Landsat5 and Landsat8 data to retrieve land surface temperature (LST). Then, the LST data were verified by using three geophysical methods which are 2-D resistivity imaging, magnetic and ground penetrating radar (GPR) methods. An unmanned aerial vehicle (UAVs) was also used to capture the aerial photos of the SB2 area to produce the digital surface model (DSM). SB2ZZ, SB1 and SB2 areas show the results of high resistivity and magnetic values which are ≥5000 Ωm and ≥50 nT respectively. The high resistivity and magnetic values indicate the interesting anomaly which is clay bricks due to the effect of heat at high temperature. Thus, the results of two geophysical methods show the potential of buried structures leading to an excavation at SB2ZZ area.